2003
DOI: 10.1034/j.1600-065x.2003.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation‐induced cell death in T cells

Abstract: A properly functioning immune system is dependent on programmed cell death at virtually every stage of lymphocyte development and activity. This review addresses the phenomenon of activation-induced cell death (AICD) in T lymphocytes, in which activation through the T-cell receptor results in apoptosis. AICD can occur in a cell-autonomous manner and is influenced by the nature of the initial T-cell activation events. It plays essential roles in both central and peripheral deletion events involved in tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
441
1
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(463 citation statements)
references
References 123 publications
11
441
1
10
Order By: Relevance
“…It serves as a death factor during immune response termination by AICD 31 and for the establishment of immune privileged tissues. 32 Genetic defects of Fas/FasL-associated apoptosis pathways lead to autoimmune lymphoproliferative syndromes in mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…It serves as a death factor during immune response termination by AICD 31 and for the establishment of immune privileged tissues. 32 Genetic defects of Fas/FasL-associated apoptosis pathways lead to autoimmune lymphoproliferative syndromes in mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, a fraction of low-affinity self-reactive T cells may escape thymic negative selection [30], and thus, to avoid autoimmunity, a range of additional tolerogenic mechanisms are required in the periphery. Indeed, peripheral mechanisms such as anergy [31], peripheral deletion [32] or suppression by regulatory T cells [33] have been described. It was recently reported that the number and functionality of Aire -/-regulatory T cells were intact [28].…”
Section: Introductionmentioning
confidence: 99%
“…Induction of FasL expression has been implicated in drug-and stress-induced apoptotic death of T lymphocytes. 7 Upon stimulation, Fas undergoes trimerization and recruits the proapoptotic adapter protein Fas-associated death domain (FADD) and pro-caspase-8, also called FADDlike interleukin 1 b-converting enzyme (FLICE), to form a death-inducing signaling complex (DISC). [8][9][10][11] Recruitment of pro-caspase-8 to the DISC leads to its proteolytic activation to caspase-8, followed by initiation of a caspase cascade leading to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…17 In fact, the susceptibility of T lymphocytes to Fas-mediated apoptosis correlates with c-FLIP levels, which are elevated during the early stages of activation but are significantly reduced upon re-stimulation when the T cells undergo AICD. 7,18,19 The molecular mechanisms involved in the regulation of expression of c-FLIP in T lymphocytes are not completely understood.…”
Section: Introductionmentioning
confidence: 99%